2013
DOI: 10.1021/ja403582u
|View full text |Cite
|
Sign up to set email alerts
|

Amine Oxidation Mediated by Lysine-Specific Demethylase 1: Quantum Mechanics/Molecular Mechanics Insights into Mechanism and Role of Lysine 661

Abstract: We report classical molecular dynamics (MD) simulations and combined quantum mechanics/molecular mechanics (QM/MM) calculations to elucidate the catalytic mechanism of the rate-determining amine oxidation step in the lysine-specific demethylase 1 (LSD1)-catalyzed demethylation of the histone tail lysine (H3K4), with flavin adenine dinucleotide (FAD) acting as cofactor. The oxidation of substrate lysine (sLys) involves the cleavage of an α-CH bond accompanied by the transfer of a hydride ion equivalent to FAD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 57 publications
11
63
0
Order By: Relevance
“…For example, Skarpeli-Liati et al [39] have reported an average 15 N isotope effect of 0.998 ± 0.004 for the one electron oxidation of N-methyl- and N, N-dimethylbenzylamines. This is consistent with calculated values of 0.996–0.998 for the formation of the nitrogen radical [8, 40]. In contrast, the average of reported 15 (k cat /K m ) values for flavin amine oxidases is 0.992 ± 0.005 [4043], in good agreement with the value of 0.992–0.993 calculated for a hydride transfer mechanism [8, 40].…”
Section: Discussionsupporting
confidence: 88%
“…For example, Skarpeli-Liati et al [39] have reported an average 15 N isotope effect of 0.998 ± 0.004 for the one electron oxidation of N-methyl- and N, N-dimethylbenzylamines. This is consistent with calculated values of 0.996–0.998 for the formation of the nitrogen radical [8, 40]. In contrast, the average of reported 15 (k cat /K m ) values for flavin amine oxidases is 0.992 ± 0.005 [4043], in good agreement with the value of 0.992–0.993 calculated for a hydride transfer mechanism [8, 40].…”
Section: Discussionsupporting
confidence: 88%
“…The system was coupled to a Nose-Hoover thermostat at 300 K [22]. The MD methodology was in most aspects identical to the one described in detail in a previous study [23].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a conserved lysine residue (Lys296 in MAO B, Lys305 in MAO A) is located in a solvent-inaccessible hydrophobic area of the active site, establishing a well conserved Lys-water-N5 motif that is also found in other oxidases. 19 However, this conserved motif would be expected to fluctuate, with water molecules easily leaving and entering the active site, since the free energy cost linked to water displacement from and to the active site is small relative to the chemical step. In this situation, the lysine amino group should be subjected to strong electrostatic effects that might alter its acid/base equilibrium.…”
mentioning
confidence: 99%